CRP, IL-6 and depression: a systematic review and meta-analysis of longitudinal studies. - Valkanova, V; Ebmeier, K; Allan, C (2013)
BACKGROUND: Inflammatory markers are raised in cross-sectional studies of depressed patients and may represent an important mediating factor for behaviour, neural plasticity and brain structure. METHODS: We undertook a systematic review of longitudinal studies, investigating whether raised inflammatory markers indicate an increased risk of subsequent depressive symptoms. We searched three databases (1970-2012) for longitudinal studies with repeat data on CRP or IL-6 levels and subsequent depressive symptoms. We calculated effect sizes using a mixed-effects model, with separate meta-analyses for inflammatory markers and age groups. RESULTS: We identified eight papers for CRP (14,832 participants) and three for IL-6 (3695 participants). There was a significant association between increased CRP and depressive symptoms (weighted-mean effect size 'unadjusted r'=0.069, p<0.0005; 'adjusted r'=0.046, p<0.0005), with moderate heterogeneity between studies (Q=11.21, p=0.08, I(2)=46.5). For IL-6 the weighted-mean effect size was smaller ('unadjusted r'=0.045, p-value=0.007; 'adjusted r'=0.097, p-value=0.06). LIMITATIONS: The meta-analysis was based on a relatively small number of studies (particularly for IL-6) and only two inflammatory markers. There was moderate heterogeneity between studies and some evidence of publication bias. CONCLUSIONS: Raised inflammatory markers have a small but significant association with the subsequent development of depressive symptoms. This is a robust effect which remains significant after adjustment for age and a wide range of factors associated with risk for depression. Our results support the hypothesis that there is a causal pathway from inflammation to depression.